The Manager Coach - Supernova (Cambridge Grove Supernova Learning Solutions, 2011)
Video: The Manager as Coach video is a work-based drama (14 mins). It shows how a manager, Yvonne, learns that adopting a more inclusive emotionally intelligent approach to coaching has positive outcomes, enabling her to find a solution to a staffing issue. The Video demonstrates how coaching can be an inspirational and motivational way of managing people rather than just a means of addressing performance
The Manager as Coach DVD contents: Main Programme (14 mins), Setting the context, Coaching attitude (1), What coaching is NOT, Coaching attitude (2) Coaching framaework Coaching skills What coaching is Not Coaching attitude (2)
Keywords: Management